Intratumoral CD73: An immune checkpoint shaping an inhibitory tumor microenvironment and implicating poor prognosis in Chinese melanoma cohorts - Gao, Zixu; Wang, Lu; Song, Zhengqing; Ren, Ming; Yang, Yang; Li, Jianrui; Shen, Kangjie; Li, Yinlam; Ding, Yiteng; Yang, Yanwen; Zhou, Yuhong; Wei, Chuanyuan; et al. (Frontiers in Immunology, 2022)
Background: As a novel immune checkpoint, CD73 has been reported to play prominent roles in several malignancies. However, the significance of CD73 in melanoma remain ambiguous. This study aimed to reveal the role of CD73 on the tumor microenvironment (TME) and patients’ prognosis, and to investigate whether CD73 could be a therapeutic target in Chinese melanomas, which were dominated by acral and mucosal subtypes. Methods: Two independent Chinese cohorts of 194 patients with melanoma were enrolled. CD73 and PD-L1 expression as well as CD8+ and CD56+ cell infiltrations were evaluated by immunohistochemistry in 194 resected melanoma samples. Clinical outcomes of patients were evaluated using the Kaplan-Meier plotter and Cox proportional hazard analysis. RNA-seq data was obtained from TCGA database. GO, KEGG and GSEA analyses were used to perform gene set functional annotations. CIBERSORT, ssGSEA and TIMER were used to explore the association between CD73 and immune infiltration. These findings were validated by establishing tumor xenograft model, and functions of tumor-infiltrating immune cells were examined by flow cytometry and immunofluorescence. Results: High CD73 expression showed poorer clinical outcomes and was identified as an independent prognostic indicator for survival in two cohorts. Expression of CD73 was more frequent than PD-L1 in Chinese melanoma cohorts (54.6% vs 23.2%). Co-expression of both immune checkpoints was infrequent (12.9%) in melanoma, and 54.4% of PD-L1 negative cases showed elevated expression of CD73. CD73high tumors showed a microenvironment with fewer CD8+ T cells and CD56+ NK cells infiltration, which displayed a dysfunctional phenotype. With the treatment of CD73 inhibitor APCP, the infiltration of CD8+ T cells and CD56+ NK cells in tumors was elevated and the immunosuppressive effect of CD73 was eliminated. Conclusions: High CD73 expression was associated with an inhibitory TME and adverse clinical outcomes of melanoma. Compared with PD-L1, CD73 was more prevalent and possessed more explicit prognostic significance. It thus could represent a prognostic indicator and potential immunotherapeutic target next to PD-L1 in melanoma for Chinese population.